Preparasi periodontal pada pembuatan gigitiruan Periodontal preparation in denture making - Sri Lelyati C. Masulili; Yulianti Kemal; Chaidar Masulili (Journal of Dentomaxillofacial Science, 2013)
Periodontal health of prosthodontic patients should be maintained to support the succeed of prosthodontic treatment.The purpose of periodontal preparation i.e. examination and diagnose of periodontal disease/condition and itstreatment; the need of preprosthetic periodontal surgery is to support the succeed of prosthodontic treatment. It’sincluded the quality, quantity, and topography of periodontium and alveolar mucosa, occlusal traumatism, toothmobility, and the need of mucogingival surgery, crown lengthening, ridge augmentation etc. The prosthetic proceduresshould be done with fully aware of the periodontal health i.e. the roughness of denture surface, the place and conditionof marginal restoration, contact point, and improper the contour of restoration. It is concluded that to support thesucceed of prosthodontic treatment, periodontal preparation should be planned and carried out before prosthodonticprocedures.